Environmental Foundations in Germany - Thomas Krikser; Bettina Matzdorf (SAGE Open, 2015)
Foundations in Germany were examined in the context of environmental issues. Data from environmental foundations show that there is huge difference between private and public foundations concerning financial settings. Furthermore, environment is often not the only objective and sometimes not even processed. Our analysis shows that there are different types of foundations with regard to environmental scopes and activities. Although “attractive topics” such as biodiversity and landscape conservation seem to be more important to foundations, less visible topics such as pollution prevention remain merely a “blind spot.” Together, these findings suggest that there is only a limited potential of private foundations compared with public foundations. Nevertheless, there might be an impact on environmental awareness and local sustainability.